Role of Communication and Marital Acceptance in Marital Adjustment for Dual Earners Married under 10 Years - Doho, Saraswati Stefannie; Setiawan, Jenny Lukito (Makara Human Behavior Studies in Asia, 2022)
This study aims to determine the role of communication and marital acceptance in marital adjustment for dual earners married under 10 years. A total of 93 respondents are involved in this study. The criteria for selecting respondents are married employees of company X in Surabaya; married under 10 years; have a working spouse. A quantitative research method with a correlational design is used. Communication, marital acceptance, and marital adjustment scales are also used. Multiple linear regression analysis shows that communication and marital acceptance have a significant role in marital adjustment. The contribution of communication and marital acceptance to marital adjustment is 54% (p < 0.05, R2 = 0.540). Thus, communication and marital acceptance predict marital adjustment. This research is expected to be useful for married couples, counselors, and prospective married couples.